Knowledge, attitude and practices toward leptospirosis among the farmers in Ma-Eliya, Kurunegala - Hewarathna, B.P.; Shopijen, E.; Jayarathne, S.W.C.R.; Chamara, W.I.; Lakmali, W.S.D.; Nizran, S.M.; Sampath, V.W.A.; Weerawarna, A.W.K.S.; Amarasinghe, T.S.; Premakumara, G.A.S. (University of Colombo, 2023)
Background: Leptospirosis is a major zoonotic disease caused by the bacteria leptospira which is considered as a public health threat globally. Poor Knowledge, Attitude and Practices (KAP) towards this disease can lead to increased morbidity and mortality. Objective: To assess the KAP related to leptospirosis among the farmers in Ma-Eliya, Kurunegala district. Methodology: A descriptive, cross-sectional study was conducted among 327 farmers in Ma-Eliya, Kurunegala, Sri Lanka. A pretested, interviewer-administered questionnaire was used to assess the KAP toward leptospirosis. Cutoff scores for knowledge were 75%, 50-74%, and 50%, which were regarded as good, satisfactory, and poor respectively. For attitudes toward leptospirosis, ≥ 70% was considered as satisfactory and < 70% unsatisfactory, while ≥ 60% was considered as satisfactory and < 60% unsatisfactory for practices on leptospirosis. Data analysis of the data was done using SPSS version 26.0. The level of significance was considered to be p<0.05. Results: The majority of the study participants were male (69.70%). The mean age of the farmers was 50.49 ±12.34. The majority of the study participants (60.6%) had been educated about leptospirosis by the Public Health Inspector. It was found that most of the study participants (82.60%) had poor knowledge 37.38±12.86 related to symptoms, transmission, complications and prevention of the disease. Unsatisfactory attitudes were demonstrated by the majority of the participants (43.63%) and 58.15% of the farmers showed unsatisfactory practices towards disease prevention. Gender was statistically significantly associated with the level of knowledge (p=0.003), attitude (p=0.014) and practices (p=0.001) regarding leptospirosis. Conclusion: The overall knowledge regarding leptospirosis was poor, while attitude and practices of the farmers of Ma-Eliya were unsatisfactory. Thus, improvement in knowledge needs to be achieved through health education sessions and information dissemination which could lead to improved attitude and practices towards the management and control of leptospirosis.
Keywords: Attitude; Farmers; Knowledge; Leptospirosis; Practice